2014
DOI: 10.1186/1745-6215-15-444
|View full text |Cite
|
Sign up to set email alerts
|

The effect on knee-joint load of instruction in analgesic use compared with neuromuscular exercise in patients with knee osteoarthritis: study protocol for a randomized, single-blind, controlled trial (the EXERPHARMA trial)

Abstract: BackgroundKnee osteoarthritis (OA) is a mechanically driven disease, and it is suggested that medial tibiofemoral knee-joint load increases with pharmacologic pain relief, indicating that pharmacologic pain relief may be positively associated with disease progression. Treatment modalities that can both relieve pain and reduce knee-joint load would be preferable. The knee-joint load is influenced by functional alignment of the trunk, pelvis, and lower-limb segments with respect to the knee, as well as the groun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 77 publications
(112 reference statements)
0
34
0
1
Order By: Relevance
“…Online supplementary appendices provided with comprehensive text descriptions and photographs or videos for each exercise26 44 45…”
Section: Resultsmentioning
confidence: 99%
“…Online supplementary appendices provided with comprehensive text descriptions and photographs or videos for each exercise26 44 45…”
Section: Resultsmentioning
confidence: 99%
“…In this context, experimental and clinical studies have investigated the effects of physical exercise training and electrophysical treatments, such as LLLT, on osteoarthritic cartilage tissue 20e23 . Several authors have suggested that exercises such as joint-specific strength and general aerobic conditioning are effective for OA treatment 10,14,15 . Moreover, some authors demonstrated that LLLT was able of decreasing the level of cartilage damage and producing a better tissue structure, biomodulating the inflammatory process and reducing swelling 2,27,29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…More recently, more innovative therapeutic approaches have been developed, aiming to avoid and to reduce joint damage and, consequently, the minimization of the functional restrictions in affected joint is of extreme clinical importance 7 . Among the innumerable range of therapeutic interventions, the positive effects of physical exercise programs on cartilage metabolism can be highlighted 8,9 . Physical exercise focusing on muscle strengthening or on aerobic activity, is an effective, low-cost and accessible therapeutic modality and might play a crucial role in the prevention and treatment of OA 4,10,11 . It is well established that regular physical exercise can improve function and reduce pain and muscle fatigue 10e13 .…”
Section: Introductionmentioning
confidence: 99%
“…The full list of inclusion and exclusion criteria is available from the published study protocol. 7 All participants provided written informed consent, and the study was approved by the regional Committee for Medical Research Ethics (project-ID: S-20110153) and the Danish Data Protection Agency (journal-ID: 2011-41-7045).…”
Section: Case Descriptionmentioning
confidence: 99%
“…However, a detailed NEMEX treatment strategy for patients with mild to moderate KOA has not been described except in the protocol paper of our study. 7 The primary aims of the NEMEX program, to improve sensorimotor control and functional joint stabilization (ie, quality of movement), differ from those of traditional osteoarthritis programs, which have a main goal of improving cardiovascular output (ie, walking programs) or enhancing muscle strength (ie, strength training with machines). 3,8 The NEMEX-KOA program that we describe was designed for physically active, middle-aged patients with mild to moderate KOA; therefore, it involves exercises and difficulty levels that are more challenging than in the previously described NEMEX program for total joint replacement.…”
mentioning
confidence: 99%